The effect of education based on the health belief model in improving anxiety among mothers of infants with retinopathy of prematurity - Azam Salehnezhad; Hamidreza Zendetalab; Shoeibi Naser; Hamidreza Behnam Voshni; Mojtaba Abrishami; Mohmmadreza Ansari Astaneh; Belin Tavakkoli Sani; Zahra Emami Moghadam (Journal of Education and Health Promotion, 2022)
BACKGROUND: Due to the role of education in improving anxiety and essential skills of mothers for caring for their infants, this study aimed to investigate the effect of education based on the health belief model (HBM) on anxiety among mothers of infants with retinopathy of prematurity (ROP). MATERIALS AND METHODS: This randomized controlled clinical trial was performed on 67 mothers with premature infants admitted to the ROP unit of Khatam Al Anbia Eye Hospital in Mashhad, Iran from 2019 to 2020. Participants were randomly allocated to intervention and control groups. Intervention was designed based on HBM during six sessions, each of 45–60 minutes duration. The control group received routine educations according to the hospital policies. The maternal anxiety, adherence with follow-up examinations and the rate of neonatal retinal vascularization were evaluated using an HBM- based questionnaire and State-Trait Anxiety Inventory questionnaire and checklists, respectively. Data was analyzed by using SPSS software, version 16, using Chi-squared test, Fisher's exact test, independent t test, and Mann–Whitney U test. RESULTS: Based on our findings, no significant difference was observed between the two groups before the intervention regarding the mean score of maternal anxiety (P = 0.141). However, after intervention, the mean score of maternal anxiety decreased significantly from 67.0 ± 6.3 to 38.5 ± 6.6 in the intervention group and increased from 69.8 ± 3.1 to 68.3 ± 3.4 in the control group (P < 0.001). In the intervention group, the mean scores of model constructs (perceived susceptibility and severity, perceived benefits, barriers, self-efficacy and cue to action) increased significantly after intervention (P < 0.001). CONCLUSIONS: Education based on HBM appear to be an efficient method to improve maternal anxiety among mothers of infants with retinopathy of prematurity. Accordingly, nurses and treatment staff can provide interventions in the NICU based on the HBM to the parents of hospitalized and premature infants.